Aplasia cutis congenita: a case report - SAKSHI,; PRAVEEN KUMAR RATHORE, (International Journal of Pharma and Bio Sciences, 2017)
Aplasia cutis congenita (ACC) is a congenital disease characterized with absence of skin usually on the scalp. No definite etiology is known however, multiple contributing factors such as intrauterine infection, fetal exposure to cocaine, heroin, alcohol or antithyroid drugs, teratogens, vascular disruption, genetic causes have been implicated. We report a neonate with an isolated lesion on the scalp in the form of a superficial ulcer which was covered with a thin membrane. There was